A Rapid and Sensitive UPLC-MS/MS Method for Quantifying Capmatinib in Human Liver Microsomes: Evaluation of Metabolic Stability by In Silico and In Vitro Analysis - Mohamed W. Attwa; Ali S. Abdelhameed; Aishah M. Alsibaee; Adnan A. Kadi (Separations, 2023)
Capmatinib (CMB) is an orally bioavailable mesenchymal–epithelial transition (MET) inhibitor approved by the US-FDA to treat metastatic non-small cell lung cancer (NSCLC) patients, with MET exon 14 skipping mutation. The current study aimed to establish a specific, rapid, and sensitive ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) analytical method for quantifying CMB in human liver microsomes (HLMs), with therapeutic implications for assessing metabolic stability. Validation of the UPLC-MS/MS analytical method in the HLMs was performed using selectivity, sensitivity, linearity, accuracy, precision, extraction recovery, stability, and matrix effects according to the guidelines for bio-analytical method validation of the US-FDA. CMB was ionized by positive electrospray ionization (ESI) as the ionization source and analysed using multiple reaction monitoring (MRM) as the mass analyser mode. CMB and pemigatinib (PMT) were resolved on the C18 column, with an isocratic mobile phase. The CMB calibration curve showed linearity in the concentration range of 1–3000 ng/mL. The intra- and inter-day accuracy and precision were −7.67–4.48% and 0.46–6.99%, respectively. The lower limit of quantification (LLOQ) of 0.94 ng/mL confirmed the sensitivity of the UPLC-MS/MS analytical method. The intrinsic clearance (Clint) and in vitro half-life (t1/2) of CMB were 61.85 mL/min/kg and 13.11 min, respectively. CMB showed a high extraction ratio. The present study is the first to develop, establish, and standardize UPLC-MS/MS for the purpose of quantifying and evaluating the metabolic stability of CMB.